2019
DOI: 10.7554/elife.41235
|View full text |Cite
|
Sign up to set email alerts
|

Statistical structure of locomotion and its modulation by odors

Abstract: Most behaviors such as making tea are not stereotypical but have an obvious structure. However, analytical methods to objectively extract structure from non-stereotyped behaviors are immature. In this study, we analyze the locomotion of fruit flies and show that this non-stereotyped behavior is well-described by a Hierarchical Hidden Markov Model (HHMM). HHMM shows that a fly's locomotion can be decomposed into a few locomotor features, and odors modulate locomotion by altering the time a fly spends performing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…Since each state lasts 1 second on an average, it implies that the fly makes one decision (in selecting speed and curvature) every second on average. This feature of the model is consistent with the Hierarchical Hidden Markov Model (HHMM) employed in a previous study [37]. HHMM showed that the fly moved at similar speed and curvature over long durations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Since each state lasts 1 second on an average, it implies that the fly makes one decision (in selecting speed and curvature) every second on average. This feature of the model is consistent with the Hierarchical Hidden Markov Model (HHMM) employed in a previous study [37]. HHMM showed that the fly moved at similar speed and curvature over long durations.…”
Section: Discussionsupporting
confidence: 87%
“…2 (see Methods for details) by sampling from speed, curvature and duration distributions for each state (S3 Fig and S4 Fig). Consistent with previous work [27,37], the behavior of the fly is different inside the light-zone and outside it, therefore three different distributions were used to model the fly's behavior-before the presence of light, during-inside and during-outside. The duration that each transition lasted was also selected from the empirical distribution (S3 Fig and S4 Fig).…”
Section: Plos Computational Biologymentioning
confidence: 90%
See 1 more Smart Citation
“…Although searches triggered by sugar, water, and odor sensation appear broadly similar in our experiments (Figures 1C, 2H and 2J), it is likely that their underlying behavioral structure differs [26,44]. For example, we found that whereas activation of Gr43a-, Gr5a-Ir76b-, ppk28-, or NPF-GAL4 results in a drop in locomotor rate or complete stopping, activation of ACV-odor-sensing Or42b-GAL4 neurons only elicits a brief startle response similar to controls ( Figures S4B and S4C).…”
Section: The Extent Of Local Search Is Modulated By Starvation Statementioning
confidence: 81%
“…Each video frame was assigned a behavioral label, which was used to calculate the probabilities of using each behavioral state, as well as the probabilities of transitioning between states. The model output was also used to compute forward and side velocities as previously described 41 statistic. To assess individual differences between behavioral states, we estimated the variance of the data through bootstrapping.…”
Section: Continuous Behavioral Classificationmentioning
confidence: 99%